A compound control strategy of three‐phase Vienna rectifier under unbalanced grid voltage - Xingtian Feng (Wiley, 2021)
Abstract When traditional finite‐set predictive power control is applied to Vienna rectifier, the input current will produce a large number of third harmonics under unbalanced power network, which will seriously affect the normal operation of Vienna rectifier. This paper proposes a compound control strategy for three‐phase Vienna rectifier based on grid imbalance. And the new finite control set‐model predictive direct power control (N‐FCS‐MPDPC) is used in the inner current loop. By introducing a redefined reactive power, this method can effectively control the second harmonic of instantaneous active power and the second harmonic of instantaneous reactive power at the same time, and realizes the normal operation of Vienna rectifier under the condition of unbalanced power grid. Linear auto disturbance rejection control (LADRC) is adopted in the outer voltage loop, which overcomes the problem of voltage overshoot and slow dynamic response in PI control. Furthermore, in order to solve the difficulty of grid‐side voltage acquisition when the grid is unbalanced, a virtual flux based no‐grid voltage sensor is introduced to measure the grid voltage. Simulation, along with experimental results, is presented to show that the proposed control strategy has good robustness and fast tracking performance under the condition of power grid imbalance.